Intercultural Features of Teaching A Foreign Language - Begmatova N. A. (European Science Publishing, 2023)
There has been an increase in the importance of the cultural aspect in teaching and learning foreign languages, and teachers nowadays are supposed to stimulate the acquisition and development of intercultural competence in their students. Foreign language teaching and learning should be regarded from an intercultural perspective. The foreign language classes can be the link between the two cultures by which students have the opportunity to discover other values, mentalities, and facets of life. In doing this, a new vision should be taken into consideration, in which the teacher naturally and harmoniously combines the linguistic and cultural elements in the educational process during all types of lessons, irrespective of the topic being dealt with, or whether they focus on grammar or vocabulary issues. The culture and civilization notions must not be regarded separately, but should be integrated in the activities meant to develop the four language skills. This paper highlights the role of foreign language teachers in developing intercultural competence, the didactic activities used in forming the cadets’ intercultural competence, pointing to the way in which this competence is achieved in the military higher education environment as well.
Keywords: intercultural competence, military higher education, teaching and learning foreign languages, didactic activities.